GDF15 contributes to radioresistance and cancer stemness of head and neck cancer by regulating cellular reactive oxygen species via a SMAD-associated signaling pathway - Li, Yan-Liang; Chang, Joseph T.; Lee, Li-Yu; Fan, Kang-Hsing; Lu, Ya-Ching; Li, Yi-Chen; Chiang, Chang-Hsu; You, Guo-Rung; Chen, Hsin-Ying; Cheng, Ann-Joy (Oncotarget, 2017)
Radiotherapy is an integral part for the treatment of head and neck cancer (HNC), while radioresistance is a major cause leads to treatment failure. GDF15, a member of the TGF-β superfamily, is hypothesized to participate in various types of homeostasis. However, the potential role of this molecule in regulation of radiosensitivity remains unclear. In this study, we demonstrated that GDF15 contributed to radioresistance of HNC, as determined by both gain- and lost-of-functional experiments. These results were achieved by the induction of mitochondrial membrane potential and suppression of intracellular reactive oxygen species (ROS). We further showed that GDF15 facilitated the conversion of cancer stemness, as assessed by the promotion of CD44+ and ALDH1+ cell populations and spheroid cell formation. At molecular level, GDF15 conferred to these cellular functions was through phosphorylated SMAD1 proteins to elite downstream signaling molecules. These cellular results were further confirmed in a tumor xenograft mouse study. Taken together, our results demonstrated that GDF15 contributed to radioresistance and cancer stemness by regulating cellular ROS levels via a SMAD-associated signaling pathway. GDF15 may serve as a prediction marker of radioresistance and a therapeutic target for the development of radio-sensitizing agents for the treatment of refractory HNC.